Northward Expansion of Amblyomma americanum (Acari: Ixodidae) into Southwestern Michigan. Issue 5 (1st July 2022) - Fowler, Peter D; Nguyentran, S; Quatroche, L; Porter, M L; Kobbekaduwa, V; Tippin, S; Miller, Guy; Dinh, E; Foster, E; Tsao, J I
Abstract: Amblyomma americanum (Linnaeus) (Acari: Ixodidae) (lone star tick) is an aggressive, generalist parasite that vectors numerous important human and animal pathogens. In recent decades its geographic range has expanded northwards from endemic regions in the southeastern and southcentral United States. In 2019 five questing A. americanum ticks, comprising two life stages were detected at one site in southwestern Michigan, satisfying one CDC criterium for an established population for the first time in recent history in the state. To better characterize the extent of emerging A. americanum, we conducted active surveillance (i.e., drag sampling) in summer 2020 throughout Michigan's southern counties and detected one adult A. americanum from each of six widespread sites, including where they had been detected in 2019. A larger established population was identified at another site in Berrien County, which yielded 691 A. americanum comprising three life stages, and questing phenologies here were similar to that reported for other endemic regions. Statewide surveillance in 2021 revealed no A. americanum outside of Berrien County, but establishment criteria were met again at the two sites where established populations were first detected respectively in 2019 and 2020. These observations may represent the successful invasion of A. americanum into Michigan. Data from passive (1999–2020) and active surveillance (2004–2021) efforts, including a domestic animal sentinel program (2015–2018), are reported to provide context for this nascent invasion. Continued active surveillance is needed to help inform the public, medical professionals, and public health officials of the health risks associated with this vector.